From the Labour Question to the Labour History Question - Pearson, Chad (Labour / Le Travail, 2010)
The article reviews three books: "Making History: Organizations of Labour Historians in Britain since 1960," edited by John McIlroy, Alan Campbell, John Halstead, and David Martin; "Histories of Labour: National and International Perspectives," edited by Joan Allen, Alan Campbell, and John McIlroy; and "Rethinking U.S. Labor History: Essays on the Working-Class Experience, 1756-2009," edited by Donna Haverty-Stacke and Daniel J. Walkowitz.
Keywords: ALLEN, Joan; BOOKS -- Reviews; CAMPBELL, Alan; HALSTEAD, John; HAVERTY-Stacke, Donna T.; HISTORIES of Labour: National & International Perspectives (Book); MAKING History: Organizations of Labour Historians in Britain Since 1960 (Book); MARTIN, David; MCILROY, John; Nonfiction; RETHINKING US Labor History: Essays on the Working-Class Experience 1756-2009 (Book); WALKOWITZ, Daniel J.

The Origins of Right to Work: Antilabor Democracy in Nineteenth-Century Chicago - Pearson, Chad (Labour / Le Travail, 2016)
The article reviews the book, "The Origins of Right to Work: Antilabor Democracy in Nineteenth-Century Chicago," by Cedric de Leon.

The Enduring Significance of Black and Multiracial Working-Class History - Pearson, Chad (Labour / Le Travail, 2022)
The article reviews and comments on "Department Stores and the Black Freedom Movement: Workers, Consumers, and Civil Rights from the 1930s to the 1980s," by Traci Parker, "Toward Freedom: The Case Against Race Reductionism," by Touré F. Reed, and "Workers on Arrival: Black Labor in the Making of America," by Joe William Trotter, Jr.

Dissenting Traditions: Essays on Bryan D. Palmer, Marxism, and History - Carleton, Sean; McCoy, Ted; Smith, Julia; Finkel, Alvin; Niergarth, Kirk; Kealey, Gregory S.; Rogers, Nicholas; Pearson, Chad; Panitch, Leo; Gindin, Sam; McIlroy, John; Campbell, Alan; et al. (Working Canadians: Books from the CCLH, 2021)
The work of Bryan D. Palmer, one of North America’s leading historians, has influenced the fields of labour history, social history, discourse analysis, communist history, and Canadian history, as well as the theoretical frameworks surrounding them. Palmer’s work reveals a life dedicated to dissent and the difficult task of imagining alternatives by understanding the past in all of its contradictions, victories, and failures. Dissenting Traditions gathers Palmer’s contemporaries, students, and sometimes critics to examine and expand on the topics and themes that have defined Palmer’s career, from labour history to Marxism and communist politics. Paying attention to Palmer’s participation in key debates, contributors demonstrate that class analysis, labour history, building institutions, and engaging the public are vital for social change. In this moment of increasing precarity and growing class inequality, Palmer’s politically engaged scholarship offers a useful roadmap for scholars and activists alike and underlines the importance of working-class history. --Publisher's description